IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI DAYA TARIK WISATA PANTAI BLIMBINGSARI BANYUWANGI - Dela Wahyu Kirana; Ivo Dwi Nanda; Rafly Akhmad; Arum Pamuji; Ayu Wanda Febrian (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2025)
The growth of the tourism sector in Indonesia encourages an increase in the number of tourists, which also raises environmental challenges, especially related to waste management in tourist attraction areas. The purpose of this study is to examine the implementation of waste management policies at Blimbingsari Beach, with reference to Blimbingsari Village Regulation Number 14 of 2024. The research uses qualitative with a descriptive-analytic approach to the intended object, through interviews, direct observation, and data triangulation techniques for data validation and validity. The results of the discussion show that some policy points have been implemented, such as waste socialization and education, waste sorting, routine waste collection and transportation, involvement of village institutions, and community participation. However, some points are not optimal, especially in terms of the application of environmentally friendly waste management technology, lack of cleaning workers, and limited infrastructure, which affects the effectiveness of existing waste management. The conclusion of this study emphasizes the importance of strengthening regulations, procuring specialized cleaning personnel, and adding supporting facilities to achieve effective and sustainable waste management at Blimbingsari Beach attraction